Diagnostic Agreement between Prehospital Emergency and In-Hospital Physicians. (24th April 2019) - Ramadanov, Nikolai; Klein, Roman; Laue, Fabian; Behringer, Wilhelm
Abstract : Background . The aim of the study was to determine the diagnostic agreement between the discharge diagnosis and the suspected diagnosis by the prehospital emergency physician and to run a sensitivity analysis of the most common diagnoses by the prehospital emergency physician. Methods . The diagnostic agreement was determined by a systematic comparison of the discharge diagnosis with suspected diagnosis by the prehospital emergency physician in a period of 24 months at the emergency medical services in Bad Belzig. The diagnostic agreement of the 13 most common discharge diagnoses was compared to the remaining diagnostic agreement. The results were tested for statistical significance using the chi-squared test. Results . In 64.1% of cases included, a diagnostic agreement occurred. There was a high proportion of diagnostic agreement for hypoglycemia (97%), atrial fibrillation (87%), cramping seizure (86%), hypertensive crisis (85.5%), and syncope (81%). There was a low proportion of diagnostic agreement for chest wall pain (27%), pneumonia (32%), and cardiac decompensation (53%). Conclusions . Our attention in practice and emergency medical courses should be directed to chest pain patients and the main symptom of dyspnea, because of the high proportion of incorrect diagnoses by the prehospital emergency physician. It should be noted that 92% of incorrectly diagnosed chest wall pain cases were overestimated with an acute coronary syndrome.